Exploitings supplementary reading materials to consolidate and develop vocabulary for grade 11 English - major students at Bien Hoa Specialized High school, Hanam = Nghiên cứu về việc khai thác tài liệu đọc hiểu bổ trợ để củng cố và phát triển từ vựng cho - Nguyễn, Thị Anh Thoa (University of Languages and International Studies, 2017)
47 p. + CD-ROM